Civil Society, Religion, and the Nation : Modernization in Intercultural Context: Russia, Japan, Turkey - Steunebrink, Gerrit,; Zweerde, Evert van der, (Brill Book Archive Part 1, ISBN: 9789004472495., 2004)
Japan, Russia, and Turkey are major examples of countries with different ethnic, religious, and cultural background that embarked on the path of modernization without having been colonized by a Western country. In all three cases, national consciousness has played a significant role in this context. The project of Modernity is obviously of European origin, but is it essentially European? Does modernization imply loss of a country's cultural or national identity? If so, what is the "fate" of the modernization process in these cases? The presence of the idea and reality of civil society can be considered a real marker of Modernity in this respect, because it presupposes the development of liberalism, individualism and human rights. But are these compatible with nationalism and with the idea of a national religion? These questions are the more pressing, as Japan is considered part of the Western world in many respects, and Russia and Turkey are defining their relation to the European Union in different ways. An investigation of these three countries, set off against more general reflections, sheds light on the possibilities or limitations of modernization n a non-European context.